Valuation of Insurance Linked Securities - Dolníková, Lenka; Stádník, Bohumil; Drahokoupil, Matěj; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
The insurance-linked securitization has been brought to more attention since the natural catastrophes occurred in the form of tropical storms, that hit the coasts of United States in the 1990’s. Ever since then, the investors slowly learnt to trust the securitization in the form of transferring their risks from the insurance market to the capital market. A product that specific, however, needs a proper evaluation and the creation of a proper model has been a lasting challenge. The thesis proposes modelling approaches of the price of the insurance-linked security and shows a case study aimed at analyzing of the impact of the existence of this product in the Czech Republic on the coverage of the losses by the state.
Vedoucí práce: Bohumil Stádník
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses